3D visual cueing shortens the double support phase of the gait cycle in patients with advanced Parkinson's disease treated with DBS of the STN - Poláková, Kamila; Růžička, Evžen; Jech, Robert; Kemlink, David; Rusz, Jan; Miletínová, Eva; Brožová, Hana (PloS one, 2020)
BACKGROUND: Gait disturbances have emerged as some of the main therapeutic concerns in late-stage Parkinson's disease (PD) treated with dopaminergic therapy and deep brain stimulation (DBS). External cues may help to overcome freezing of gait (FOG) and improve some of the gait parameters. AIM: To evaluate the effect of 3D visual cues and STN-DBS on gait in PD group. METHODS: We enrolled 35 PD patients treated with DBS of nucleus subthalamicus (STN-DBS). Twenty-five patients (5 females; mean age 58.9 ±6.3) and 25 sex- and age-matched controls completed the gait examination. The gait in 10 patients deteriorated in OFF state. The severity of PD was evaluated using the Unified Parkinson's Disease Rating Scale (UPDRS) and Hoehn and Yahr (HY). The PD group filled the Falls Efficacy Scale-International (FES) and Freezing of Gait Questionnaire (FOGQ). Gait was examined using the GaitRite Analysis System, placed in the middle of the 10m marked path. The PD group was tested without dopaminergic medication with and without visual cueing together with the DBS switched ON and OFF. The setting of DBS was double-blind and performed in random order. RESULTS: The UPDRS was 21.9 ±9.5 in DBS ON state and 41.3 ±13.7 in DBS OFF state. HY was 2.5 ±0.6, FES 12.4 ±4.1 and FOGQ 9.4 ±5.7. In the DBS OFF state, PD group walked more slowly with shorter steps, had greater step length variability and longer duration of the double support phase compared to healthy controls. The walking speed and step length increased in the DBS ON state. The double support phase was reduced with 3D visual cueing and DBS; the combination of both cueing and DBS was even more effective. CONCLUSION: Cueing with 3D visual stimuli shortens the double support phase in PD patients treated with DBS-STN. The DBS is more effective in prolonging step length and increasing gait speed. We conclude that 3D visual cueing can improve walking in patients with DBS.
Keywords: výsledek terapie; podněty; hluboká mozková stimulace; Male; Gait Disorders, Neurologic; Subthalamic Nucleus; Aged; chůze (způsob); Deep Brain Stimulation; mužské pohlaví; senioři; průzkumy a dotazníky; Cues; dvojitá slepá metoda; Treatment Outcome; Gait; lidé; ženské pohlaví; neurologické poruchy chůze; Humans; nucleus subthalamicus; Double-Blind Method; Female; Parkinson Disease; Parkinsonova nemoc; Surveys and Questionnaires; lidé středního věku; Middle Aged